Menumbuh Kembangkan Green Behavior Siswa Berbasis Adiwiyata di SMP Negeri 2 Kabupaten Kuningan: Developing Students' Green Behavior Based on Adiwiyata at SMP Negeri 2 Kuningan Regency - Suherman, Aris; Suteja; Irvan Rosviana, Mohammad (ISEDU : Islamic Education Journal, 2023)
Environmental indifference remains a significant issue in today’s global era, requiring attention and solutions, such as the Adiwiyata program. One strategy to address this is fostering green behavior, starting with small, eco-friendly actions. This study aims to explore: 1) The green behavior of students at SMP Negeri 2 Kuningan, 2) The implementation of green behavior based on the Adiwiyata program, and 3) How to nurture and develop green behavior in students. Using a qualitative method with a descriptive-analytical approach, data was collected through observation, interviews, and documentation. The main informants were teachers, students, and the school principal. The findings show that: 1) Green behavior is generally formed but not yet fully integrated with the expected values. 2) Students have implemented green behavior, though some challenges remain. 3) The school fosters green behavior through curriculum development, participatory activities, and supporting infrastructure. Supportive factors include intellectual motivation, stakeholder involvement, Adiwiyata team consistency, and adequate facilities, while obstacles include budget constraints, insufficient habituation control, and a lack of connection between students, parents, and the community.